Analisis Yuridis Peran Hukum Internasional Dalam Upaya Pencegahan Pencemaran Sampah Plastik Sekali Pakai Terhadap Perlindungan Lingkungan Laut Negara Indonesia - Nanda Erlangga Pranata; Maria Maya Lestari; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Plastic pollution is a global problem and must be tackled in a sustainable manner. Oneform of effort to protect the marine environment is found in the 1982 United NationsConvention on the Law of the Sea (UNCLOS 1982) which can be seen in article 235UNCLOS 1982, and the International Convention for the Prevention of Pollution from Ships1973, (MARPOL Convention 1973), In MARPOL 1973 Annex which regulates theprevention of marine pollution from plastic waste is Annex 5 concerning the prevention ofwaste pollution from ships, contained in Regulations 3 (Disposal of Garbage Outside SpecialAreas). This study aims to determine the role of international law in regulating issues ofsingle-use plastic waste pollution against the protection of the marine environment ofIndonesia and Indonesia's role in implementing efforts to reduce single-use plastic pollutionthrough provisions of international law.This type of research includes the type of normative juridical research. To obtain datain this legal research, the authors use several approaches, namely the statute approach, caseapproach. This research uses literature research by obtaining secondary data in the form ofliterature books, research results, journals, articles, and legal regulations related to the objectof research.From the results of the research that has been done, there are two main things that canbe concluded. First, with the continuing increase in the amount of single-use plastic wastepollution in the sea, this proves that the role of UNCLOS 1982 and MARPOL 1973 has notbeen able to stop the rate of pollution that is occurring, plus UNCLOS 1982 has notspecifically regulated plastic waste, this has had a negative impact on marine biota which canalso impact the economy, health, social. Second, International Law and National Law haveregulated the prevention of environmental pollution. Both UNCLOS 1982 and Law 32 of2009 have regulated pollution prevention rules. One of the main challenges in overcomingthe problem of marine plastic waste in Indonesia is the absence of specific laws that regulatemarine plastic pollution. Even though Indonesia already has a legal basis for protecting andmanaging the marine environment, such as Law Number 32 of 2009 concerning theProtection and Management of the Environment, and Law Number 32 of 2014 concerning theSea, there is no law that specifically deals with marine plastic waste.